2002
DOI: 10.1073/pnas.232161999
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of the two heads of myosin during muscle contraction

Abstract: We have used luminescence resonance energy transfer between regulatory light chains (RLC) to detect structural changes within the dimeric myosin molecule in contracting muscle fibers. Fully functional scallop muscle fibers were prepared such that each myosin molecule contained a terbium-labeled (luminescent donor) RLC on one head and a rhodamine-labeled (acceptor) RLC on the other. Time-resolved luminescence energy transfer between the two heads increased upon the transition from relaxation (ATP) to contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…LRET, using Tb 3+ chelates bound to single-Cys RLC mutants, was used to measure distances between LCDs on the two heads of myosin in scallop muscle fibers (42) and in skeletal muscle HMM (15). In the muscle fiber study, the head-head separation was greatest in relaxation, least in rigor, and intermediate in contraction.…”
Section: Myosin Light-chain Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…LRET, using Tb 3+ chelates bound to single-Cys RLC mutants, was used to measure distances between LCDs on the two heads of myosin in scallop muscle fibers (42) and in skeletal muscle HMM (15). In the muscle fiber study, the head-head separation was greatest in relaxation, least in rigor, and intermediate in contraction.…”
Section: Myosin Light-chain Domainmentioning
confidence: 99%
“…In the muscle fiber study, the head-head separation was greatest in relaxation, least in rigor, and intermediate in contraction. Using four different labeling sites on RLC, it was found that the relative tilt of the two LCDs decreases by 30° in the force-generating weak-to-strong transition (42). The HMM study concluded that the two heads of myosin bind to actin in rigor in a strained configuration that is distinct from that of single-headed binding (15).…”
Section: Myosin Light-chain Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively early work showed that mollusc myosin has the typical two headed structure of other myosins (Elliott et al, 1976), that in the rest state ADP binds to both heads (Marston and Lehman, 1974;Shibata-Sekiya, 1982), that ATP binding alters tryptophan fluorescence (Kondo et al, 1979;, that a tryptophan present in the skeletal ATP binding site is replaced in scallop by an arginine (Kondo et al, 1979;Kerwin and Yount, 1992), and identified portions of the heavy chain and myosin head required for ATPase activity (Szentkiralyi, 1987) and actin binding (Castellani et al, 1987). Electron paramagnetic resonance showed that force generation (but not ATP hydrolysis) is associated with light chain rotation (Baker et al, 1998;Roopnarine et al, 1998;Cooke, 1998;BrustMascher et al, 1999;LaConte et al, 2003), and measurement of luminescence resonance energy transfer between the regulatory light chains showed that the light chains of both heads rotate together to act as a coordinated lever arm (Lidke and Thomas, 2002).…”
Section: 32mentioning
confidence: 99%
“…One of these states (denoted AM*ADP) is separated from the actual ADP-release step by a strain-dependent isomerization (5,6,16,21). Since a similar state has been implicated as being critical for the processivity of nonmuscular myosins (e.g., myosin V (22)), it is of interest to consider the possibility that processivity may also occur with myosin II (6,13,(23)(24)(25)(26), and that the AM*ADP state may play a role in this connection.…”
Section: Introductionmentioning
confidence: 99%